2021
DOI: 10.1071/cp21102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different genotypes of

Abstract: Tithonia diversifolia (Mexican sunflower) is a shrub used for animal feed that has outstanding agronomic and chemical characteristics. Its potential to modify the dynamics of fermentation and improve the supply of nutrients to ruminants has received considerable attention. This study was designed to determine the effect of different genotypes of T. diversifolia on ruminal fermentation and degradation of dry matter (DM), concentration of volatile fatty acids, and production of methane (CH4) when mixed with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Unfortunately, there is not much work in the literature describing the IVGP kinetics of TD inclusion in concentrate diets, although some authors have described its kinetic behavior in forage diets. Firsoni et al [46] reported a gas production rate of 0.038 h −1 for a substrate using 75% T. diversifolia and 25% rice bran, values similar to our highest TD inclusion, and Rivera et al [47] reported that B. brizantha, in association with different genotypes of TD, had a specific gas accumulation rate between 0.09 and 0.1 h −1 , values higher Some authors argue that the only really valuable information gained from gas production alone is the fermentation rates [44,45]. In the present study, no major differences were observed in the gas production rates (k) between the different substrates; nonetheless, the tendency in the increasing k and the differences in µ 0.5 are consistent with the results obtained in the IVDOM, discussed later, granted that the latter results were more conclusive.…”
Section: In Vitro Fermentation Kineticssupporting
confidence: 86%
See 2 more Smart Citations
“…Unfortunately, there is not much work in the literature describing the IVGP kinetics of TD inclusion in concentrate diets, although some authors have described its kinetic behavior in forage diets. Firsoni et al [46] reported a gas production rate of 0.038 h −1 for a substrate using 75% T. diversifolia and 25% rice bran, values similar to our highest TD inclusion, and Rivera et al [47] reported that B. brizantha, in association with different genotypes of TD, had a specific gas accumulation rate between 0.09 and 0.1 h −1 , values higher Some authors argue that the only really valuable information gained from gas production alone is the fermentation rates [44,45]. In the present study, no major differences were observed in the gas production rates (k) between the different substrates; nonetheless, the tendency in the increasing k and the differences in µ 0.5 are consistent with the results obtained in the IVDOM, discussed later, granted that the latter results were more conclusive.…”
Section: In Vitro Fermentation Kineticssupporting
confidence: 86%
“…Unfortunately, there is not much work in the literature describing the IVGP kinetics of TD inclusion in concentrate diets, although some authors have described its kinetic behavior in forage diets. Firsoni et al [46] reported a gas production rate of 0.038 h −1 for a substrate using 75% T. diversifolia and 25% rice bran, values similar to our highest TD inclusion, and Rivera et al [47] reported that B. brizantha, in association with different genotypes of TD, had a specific gas accumulation rate between 0.09 and 0.1 h −1 , values higher than those obtained in the present study.…”
Section: In Vitro Fermentation Kineticssupporting
confidence: 81%
See 1 more Smart Citation
“…Since N 2 O emissions are traditionally higher in urine, this may be a mitigation pathway. Silvopastoral systems use forage species such as Leucaena leucocephala, Tithonia diversifolia, and Gliricidia sepium, which contain significant amounts of tannins in their leaves and stems (Barahona et al, 2006;Rivera et al, 2021). Rivera et al (2018) compared an iSPS and a traditional system and found reductions in emission factors (N 2 O) of 23% and 10 times less for feces and urine, respectively.…”
Section: Implementation Of Silvopastoral Systemsmentioning
confidence: 99%
“…T. diversifolia has been used as forage source in silvopastoral arrangements or as cut-and-carry forage (Mauricio et al 2014;Palmer 2014). It exhibits greater biomass production and nutritional value compared to tropical grasses and demonstrates broad adaptability to different edaphoclimatic conditions, with the potential to enhance animal productivity by improving fermentative e ciency and reducing enteric methane (CH 4 ) emissions (Rivera et al 2021(Rivera et al , 2022Mahecha et al 2022).…”
Section: Introductionmentioning
confidence: 99%